The service required quality ensure model of LTE technology downlink - Garkusha, Sergey; Al-Dulaimi, Aymen Mohammed Khodayer; Al-Janabi, Haider Dheyaa Kamil (Eastern-European Journal of Enterprise Technologies, 2013)
Article presents a mathematical model of resource blocks distribution in LTE technology downlink. Offered model aims at providing guaranteed quality of service wireless users by user stations allocating of required transmission rates. Comparative analysis of obtained solutions by using different objective functions. Using various kinds of objective functions in offered model is directed to resource blocks allocation of minimum downlink or a minimum data transmission rate of each user station. It was found the greatest savings of time frequency resource allows objective function aimed at minimizing number of used resource blocks. The model offered in classes of service CoS corresponds to Class B each providing each user station a guaranteed transmission rate, with access to additional (nonguaranteed) bandwidth